Are Muscle Strength and Function of the Uninjured Lower Limb Weakened After Anterior Cruciate Ligament Injury? Two-Year Follow-up After Reconstruction - Chung, Kyu Sung; Ha, Jeong Ku; Yeom, Cheol Hyun; Ra, Ho Jong; Lim, Jin Woo; Kwon, Min Soo; Kim, Jin Goo (The American journal of sports medicine, 2015)
After an anterior cruciate ligament (ACL) injury, the uninjured contralateral lower limb may become weakened because of neuromuscular changes, proprioceptive deficits, and disuse of the limb; this weakness predisposes the limb to ACL injury. However, no results have been reported regarding weakness in the contralateral limb after ACL injury. Muscle strength and functional status of the contralateral lower limb are reduced after unilateral ACL injury. Cohort study; Level of evidence, 3. The ACL group consisted of 75 patients who underwent primary unilateral ACL reconstruction and were followed at 3, 6, 12, and 24 months postoperatively. A group of 75 healthy individuals (controls) were matched one-to-one with the ACL group for age, sex, body mass index, and initial Tegner activity level. The side that was evaluated in each control subject corresponded to the injured limb in the matched ACL subject. Isokinetic muscle strength, including extension peak torque per body weight (EPT) and flexion peak torque per body weight (FPT), was evaluated at angular velocities of 60 and 180 deg/s. Patients were also evaluated by single-legged hop test. Compared with the EPT at 60 deg/s in the control group (290.9 ± 40.1 N · m/kg), the value in the ACL group 24-month follow-up (276.6 ± 42.8 N · m/kg) as well as other follow-up times was significantly lower (P < .05), whereas the EPT at 180 deg/s and the FPT at 60 and 180 deg/s in the ACL group were significantly lower than the control group at 3-month follow-up but were restored to normal levels at final follow-up. Results from the single-legged hop test demonstrated that the ACL group performed at a significantly lower level than the control group at 24-month follow-up (158.4 ± 25.3 vs 176.3 ± 24.7 cm; P < .05) as well as other follow-up times. However, both measurements improved significantly as the follow-up time progressed. After ACL injury, isokinetic extensor muscle strength and functional status of the contralateral limb were reduced, even at 24 months after ACL reconstruction. However, both measurements improved significantly as the follow-up time progressed. In contrast, flexion muscle strength was restored to normal levels. Therefore, care should be taken to restore muscle strength and functional status in not only the ACL-reconstructed knee but also the uninjured limb.